1999
DOI: 10.1088/0022-3727/32/10/312
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to make clear the physical grounds of deviations from local thermodynamic equilibrium (LTE) in atmospheric free-burning argon arcs, the heavy particle temperature, electron temperature and LTE temperature obtained from electron number density were measured by use of line-profile analysis of the laser scattering method without an assumption of LTE. The experimental results showed that the core region of the arc significantly deviated from LTE under both conditions of 50 and 150 A in arc current. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 27 publications
(63 reference statements)
5
101
0
Order By: Relevance
“…[1][2][3] Thus, understanding the relation among the temperatures of the arc plasma, the distributions of current and heat input on the anode, and the results is quite important for the materials processing by the free-burning arcs. However, experimental and theoretical investigations of the temperature of arc plasma, [3][4][5][6][7][8][9] the distributions of current and heat input, 10,11) and results, for example, the weld penetration [12][13][14][15][16] were separately conducted and the relation among them has not been made clear. For example, Nestor 10) measured the distributions of current and heat input on the anode of freeburning arc by using the water-cooled copper anode which consists of two separate blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Thus, understanding the relation among the temperatures of the arc plasma, the distributions of current and heat input on the anode, and the results is quite important for the materials processing by the free-burning arcs. However, experimental and theoretical investigations of the temperature of arc plasma, [3][4][5][6][7][8][9] the distributions of current and heat input, 10,11) and results, for example, the weld penetration [12][13][14][15][16] were separately conducted and the relation among them has not been made clear. For example, Nestor 10) measured the distributions of current and heat input on the anode of freeburning arc by using the water-cooled copper anode which consists of two separate blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is expected that this region consists of metal vapor and information about the concentration of metal vapor is nothing. Fortunately, Tanaka and Ushio [11] found that LTE temperature was in accordance with the electron temperature in the region close to the anode. On the other hand, as showed in Fig.…”
Section: Technique For Density Measurementmentioning
confidence: 85%
“…The theory of Thomson scattering is explicated by many literatures [7][8][9][10][11]13]. Figure 2 shows the comparison between electron temperature for the pure helium arc with the water-cooled copper anode (left side) and that for the helium arc during welding (right side) under the same condition of 150 A in arc current and 5 mm in arc length.…”
Section: Temperature Distributions 21 Experimental Set Upmentioning
confidence: 99%
See 2 more Smart Citations